2020
DOI: 10.11645/14.2.2692
|View full text |Cite
|
Sign up to set email alerts
|

Information literacy outreach between universities and schools

Abstract: Research shows that students starting higher education (HE) often lack an essential level of information literacy (IL). To address this issue, a growing number of Higher Education Institutions (HEIs) engage with schools through Information Literacy Outreach Programmes (ILOPs). This paper explores the forces and motivations behind how and why HEIs engage with schools through ILOPs, and discusses their impact on beneficiaries. Using a UK research-led university in the North of England as a single case stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The literature also confirms that SLPs traditionally collaborate with teachers and offer instructional support on information searching, evaluation, copyright, academic integrity, citation, referencing and plagiarism awareness within the information literacy or library skills spectrum (Farmer & Phamle, 2021;Hossain, 2020;Tilke & Barrett, 2021;Vieyra & Weaver, 2016;Wagg & McKinney, 2020). Valenza et al (2022) recent study reported that high school students from schools with certified librarians, performed better in terms of understanding and using research strategies and tools and felt better prepared for academic research.…”
Section: Literature Reviewmentioning
confidence: 81%
“…The literature also confirms that SLPs traditionally collaborate with teachers and offer instructional support on information searching, evaluation, copyright, academic integrity, citation, referencing and plagiarism awareness within the information literacy or library skills spectrum (Farmer & Phamle, 2021;Hossain, 2020;Tilke & Barrett, 2021;Vieyra & Weaver, 2016;Wagg & McKinney, 2020). Valenza et al (2022) recent study reported that high school students from schools with certified librarians, performed better in terms of understanding and using research strategies and tools and felt better prepared for academic research.…”
Section: Literature Reviewmentioning
confidence: 81%
“…The literature also confirms that library professionals traditionally collaborate with classroom teachers (Wagg & McKinney, 2020) and offer instructional support on IL and AIL, such as information searching, evaluation, citation, referencing and plagiarism awareness (Farmer & Phamle, 2021;Gavigan, 2021;Hossain, 2020); how to correctly employ a certain convention and bibliographic management software (Benjes-Small et al, 2008;Morrow, 2018;Vieyra & Weaver, 2016). Similarly, in K-12, school library professionals (SLPs) are 'instructional partners' of teachers who work collaboratively to meet curriculum and IL goals (Kammer & Hays, 2021;Toerien & Harrow, 2019cited in Wagg & McKinney, 2020.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Similarly, in K-12, school library professionals (SLPs) are 'instructional partners' of teachers who work collaboratively to meet curriculum and IL goals (Kammer & Hays, 2021;Toerien & Harrow, 2019cited in Wagg & McKinney, 2020. Numerous studies have highlighted how SLPs develop the IL, transition literacy and other transdisciplinary skills of students whilst in K-12 (Smith, 2016;Streatfield et al, 2011;Wagg & McKinney, 2020), endorsing SLPs as the core members of the IL team for developing and implementing ethical education (Hossain, 2020;Williamson & McGregor, 2011) under the existing IL/transition literacy curriculum. Gavigan (2021) highlighted that SLPs collaborate with teachers to guide students to "understand the ethical use of ideas and information" including "acknowledging authorship and properly citing content" (para.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is very little North American literature on post-secondary outreach programs to high schools on academic integrity. Wagg and McKinney (2020) researchers in the UK, investigated the value of outreach programs between higher education institutions and high schools specifically looking at aspects of information literacy programming. Their findings indicate that this kind of program "is an effective mechanism for bridging the social worlds of schools and higher education; for creating partnerships and knowledge sharing between institutions; for breaking down social barriers and inequalities; and for developing critically aware, independent learners" (p. 63).…”
Section: Academic Librarians and High Schoolsmentioning
confidence: 99%
“…What makes this an effective, accessible program at the University of Calgary? Part of the effectiveness is related to what Wagg and McKinney (2020) identify as barriers. In their research schools identified "taking time out of the curriculum, staffing and resources and cost of travel" as reasons for not taking part in outreach opportunities for their students in regard to building information literacy skills (61).…”
Section: Establishing An Effective Outreach Programmentioning
confidence: 99%